Comparison between the results of bipolar hemiarthroplasty with lateral approach and posterior approach in Sanglah General Hospital in 2018: a case series - Subawa, I. Wayan; Krisna Yudha, Gede Agung; Mahardika Putra, I. Gede (International Journal of Research in Medical Sciences, 2020)
The purpose of this study was to compare the preoperative, intraoperative and postoperative parameters of Bipolar Hemiarthroplasty procedure using lateral approach and posterior approach in Sanglah General Hospital in 2018. Thirty-five patients diagnosed with femoral neck fracture or intertrochanter fracture underwent Bipolar Hemiarthroplasty using either lateral approach or posterior approach at our institution between January 2018 and December 2018. The primary outcome measures were postoperative complication and hip function. The secondary outcome measures were surgical time, transfusion rate, length of hospital stay, intraoperative blood loss and postoperative haemoglobin. There were 14 patients in Lateral Approach group and 21 patients Posterior Approach group included for analysis. There were no significant differences between the two groups regarding to the Harris Hip Score at 6 months follow up. Significant differences were found between Bipolar Hemiarthroplasty with Lateral Approach and Bipolar Hemiarthroplasty with Posterior Approach group in comparison of intraoperative blood loss (p<0.05) and length of stay (p<0.05). The present study concluded that both lateral and posterior approaches are comparable in terms of functional outcomes and complications. However, there is a tendency of longer hospital of length of stay and more of intraoperative blood loss using posterior approach which should be kept in mind when orthopaedic surgeon is performing a bipolar hemiarthroplasty.